Bonding effectiveness of multi-step adhesive resin cements to CAD/CAM blocks: impact of thermal cycling and surface treatment methods - Seda Üstün Aladağ; Elif Aydoğan Ayaz (BMC, 2024)
Abstract Background To investigate the effects of thermal cycling and surface treatment methods on the bonding effectiveness of multi-step resin cements to CAD/CAM blocks. Methods A total of 198 slices, 66 each from CAD/CAM blocks (feldspathic ceramic: Vitablocs TriLuxe Forte, V; resin matrix ceramics (RMCs): Cerasmart, C; and Shofu Block HC, S), were obtained and randomly divided into two subgroups for etching with hydrofluoric acid (HFA) and sandblasting with Al2O3 (SB). After the surface treatments, one etched and one sandblasted sample of each CAD/CAM block was observed via SEM analysis at 500× magnification. The remaining 32 etched and 32 sandblasted samples of each CAD/CAM block were divided into two subgroups to be cemented with total-etch (TE) and self-etch (SE) resin cements. Then, half of the 16 samples in all the subgroups were subjected to aging (TC) for 5000 cycles (n = 8). The shear bond strength (SBS) of each sample was measured. Four-way analysis of variance (ANOVA) and Tukey tests were used to analyze the data (p < 0.05). Results With or without TC, the highest SBS values for V were obtained with the HFA-TE and HFA-SE interactions, respectively. C presented the highest SBS values with HFA-SE and SB-TE interactions, whereas S presented the highest SBS values with SB-TE and HFA-TE interactions. Except the SB-SE interaction, C presented lower SBS values after TC than other materials. HFA created less porosity on the C and S surfaces than V. SB visibly roughened the surfaces of all the materials but caused fractures, cracks, and damage to the surfaces. Conclusion Similar SBS values can be achieved between feldspathics, RMCs, and multi-step adhesive resins with both HFA and SB treatments. However, the SBS values obtained from the SB-SE interaction may be below the recommended threshold values for all materials after TC. SB can cause distinctive cavities, fissures, and damage, especially on the surfaces of RMCs.